Coping among public safety personnel: A systematic review and meta–analysis. (17th March 2021) - Di Nota, Paula M.; Kasurak, Emily; Bahji, Anees; Groll, Dianne; Anderson, Gregory S.
Abstract: Public safety personnel (PSP) are routinely exposed to potentially psychologically traumatic events (PPTEs) that, in turn, can result in posttraumatic stress injuries (PTSI), including burnout and increased symptoms of depression and anxiety. However, the longitudinal impact of PPTEs on PSP coping remains unclear. Coping can be operationalized as various strategies (i.e., behaviours, skills, thought and emotion regulation) for dealing with stressors, which are broadly categorized as either approach (adaptive, positive, social support) or avoidant coping strategies (maladaptive withdrawal, avoidance, substance use). This systematic review and meta‐analysis aims to evaluate longitudinal coping outcomes among PSP. Thirteen eligible repeated‐measures studies explicitly evaluated coping in 1854 police officers, firefighters, and rescue and recovery workers. Study designs included randomized‐control trials, within‐subject interventions and observational studies. Effect sizes (Cohen's d ) at follow‐up were described in 11 studies. Separate meta‐analyses reveal small ( d < 0.2) but non‐significant improvements in approach and avoidant coping. Studies were of moderate quality and low risk of publication bias. Heterogeneity in outcome measures, follow‐up durations, and study types precluded subgroup analyses. The current findings can inform the development and evaluation of organizational training programs that effectively promote sustained adaptive coping for PSP and mitigate PTSIs.